Culture of everyday life: to the problem of logic of structure and content of the educational discipline. Part I - V. G. Napadysta, (Ukrainian Cultural Studies, 2021)
The article discusses the logic of structuring and content of the discipline "Culture of Everyday Life", due to the complexity and versatility of the phenomenon of everyday life and interdisciplinarity of methodological optics of its research, the variety of theoretical tools, which, in turn, determines the ambiguity of views on the very essence of the phenomenon of everyday life and its components. The analysis of educational programs on "Culture of Everyday Life", that are among the elements of educational-professional and educational-scientific training programs on "Culturology" in higher education institutions in Ukraine, demonstrated the wide variability of their content and structure. The first part of the article substantiates the need to discuss among stakeholders the boundaries and basic elements of the subject field of the discipline, which would determine its specifics and features when considering the phenomenon of everyday life. A certain model of the logical structure of the "Culture of Everyday Life" as a discipline is proposed, the main elements of its structure and their content are considered. The main stages and thematic directions of historiography of the phenomenon of everyday life in accordance with the scientific specializations of researchers are analyzed. The main achievements in the study of the everyday life phenomenon, initiated by experts of life of certain social groups representing different cultural and historical epochs, as well as the work of historians, philosophers, sociologists, carried out during the XXth century, are considered.The most common definitions of the phenomenon of everyday life, which operate in different segments of modern socio-humanitarian knowledge are analyzed, to understand the situation in modern "everyday science" in terms of systematization / structuring of accumulated knowledge about the phenomenon of everyday life, defining the boundaries of everyday life and its opposing worlds, which more clearly outline the contours of everyday life and thus contribute to the definition of the thematic field of the discipline "Culture of Everyday Life".
Keywords: the phenomenon of everyday life, the culture of everyday life, the structure of the discipline, the content of the discipline